2014
DOI: 10.1109/tns.2014.2363899
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Robustness of a COTS Soft-Error Free SRAM to Neutron Radiation

Abstract: Abstract-Radiation tests with 15-MeV neutrons were performed in a COTS SRAM including a new memory cell design combining SRAM cells and DRAM capacitors to determine if, as claimed, it is soft-error free and to estimate upper bounds for the cross-section. These tests led to cross-section values two orders of magnitude below those of typical CMOS SRAMs in the same technology node. MUSCA SEP3 simulations complement these results predicting that only high-energy neutrons (> 30 MeV) can provoke bit flips in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
21
1
Order By: Relevance
“…In a previous work, it was concluded that the SEU cross section in A-LPSRAM memories was two orders of magnitude below those of its counterparts in bulk CMOS technology [5]. However, as other authors have reported SEUs with protons and heavy ions [3], [4], it was likely that SEUs appeared at low values of bias voltage since there is evidence that, at least in bulk CMOS memories, the cross section exponentially grows as the bias voltage approaches the minimum value [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous work, it was concluded that the SEU cross section in A-LPSRAM memories was two orders of magnitude below those of its counterparts in bulk CMOS technology [5]. However, as other authors have reported SEUs with protons and heavy ions [3], [4], it was likely that SEUs appeared at low values of bias voltage since there is evidence that, at least in bulk CMOS memories, the cross section exponentially grows as the bias voltage approaches the minimum value [10].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, this accelerator has been used to irradiate integrated circuits from different technologies [5], [9]. It is an electrostatic accelerator producing neutrons by impinging a deuteron beam Neutron production is monitored throughout the experiments to determine the neutron dose for each irradiation.…”
Section: Genepi2 (Generator Of Neutrons Pulsed and Intense)mentioning
confidence: 99%
See 2 more Smart Citations
“…If . Error bars were calculated with the inverse χ 2 function, as explained in [13]. An equivalent graph, but related to the CDAV, can be found in [14].…”
Section: If Onlymentioning
confidence: 99%